Боратынский. Истинная повесть - Песков Алексей Михайлович (Писатели о писателях, 1990)
Экземпляры: аб. (ретро) / Инвентарный номер: 24427 / Цена: / Сис.шифр: 84(2=Рус)7-48 / Авт.знак: П 28 / ББК: 84(2=Рус)7-48